Surface Modification of Silk by (DBD) Dielectric Barrier Discharge Treatment for Dyeing with Natural Dye Yerba Mate (Ilex paraguariensis). (2017) - Vila, Nívea Taís; Ferreira, Alexandre; da Silva, Márcia Gomes; Fernandes, Marta; Fiori, Simone
Abstract: The objective of the current research is to study the versatility of the dielectric barrier discharge (DBD) plasma treatment for surface modification of silk fabrics dyed with yerba mate dye (Ilex paraguariensis). An analysis to check for improvement of properties regarding the penetration and fixation of natural dyes without the use of metallic mordants, that are highly toxic. The color parameters was evaluated by means of spectroscopy to evaluate color intensity, and the solidity was evaluated by tests of color fastness to washing, rubbing, sweating and light.